PREVENTION OF ANTRACYCLIN ANTIBIOTIC DOXORUBICIN СARDIOTOXICITY: A ROLE OF ACE-INHIBITOR PERINDOPRIL - E. V. Pravdivtseva; N. G. Poteshkina; A. M. Svanadze; D. S. Rilskiy (Klinicist)
Aim – to study how anthracyclines influence on cardiovascular system in patients with lymphomas and whether angiotensin-converting enzyme inhibitor Perindopril is cardioprotective in these patients.Subjects and methods. 26 patients with Hodgkin’s disease and non-Hodgkin’s lymphomas were followed before and after treatment withdoxorubicin. 12 of these patients with arterial hypertension received angiotensin-converting enzyme inhibitor Рerindopril, 10 mg/d, duringtreatment with doxorubicin. Cardiological evaluation was performed before and the next day after chemotherapy. Average dose of Doxorubicin was 34,99 ± 13,23 mg/m2.Results. In patients receiving anthracyclines deceleration time DT increased significantly, a significant reduction in heart rate (HR), cardiacoutput (CO) and cardiac index (CI) were observed also (рDT = 0,037, pHR = 0,048, рСО = 0,007, рCI = 0,007). In patients simultaneouslytreated with Perindopril these parameters were not statistically different (рDT = 0,92, pHR = 0,22, рCO = 0,35, рCI = 0,39).Conclusion. Administration of anthracyclines (average dose of Doxorubicin 34,99 ± 13,23 mg/m2) leads to DT of the left ventricle andreduction in HR, CJ and CI. Simultaneous treatment with Perindopril in patients receiving anthracyclines preserves DF and prevents heart hemodynamics abnormalities.